MIWI2 targets RNAs transcribed from piRNA‐dependent regions to drive DNA methylation in mouse prospermatogonia. (14th August 2018) - Watanabe, Toshiaki; Cui, Xiekui; Yuan, Zhongyu; Qi, Hongying; Lin, Haifan
Abstract: Argonaute/Piwi proteins can regulate gene expression via RNA degradation and translational regulation using small RNAs as guides. They also promote the establishment of suppressive epigenetic marks on repeat sequences in diverse organisms. In mice, the nuclear Piwi protein MIWI2 and Piwi‐interacting RNAs (piRNAs) are required for DNA methylation of retrotransposon sequences and some other sequences. However, its underlying molecular mechanisms remain unclear. Here, we show that piRNA‐dependent regions are transcribed at the stage when piRNA‐mediated DNA methylation takes place. MIWI2 specifically interacts with RNAs from these regions. In addition, we generated mice with deletion of a retrotransposon sequence either in a representative piRNA‐dependent region or in a piRNA cluster. Both deleted regions were required for the establishment of DNA methylation of the piRNA‐dependent region, indicating that piRNAs determine the target specificity of MIWI2‐mediated DNA methylation. Our results indicate that MIWI2 affects the chromatin state through base‐pairing between piRNAs and nascent RNAs, as observed in other organisms possessing small RNA‐mediated epigenetic regulation. Synopsis: The nuclear Piwi protein MIWI2 regulates DNA methylation of specific genomic regions in murine spermatogenic cells. Base‐pairing between MIWI2‐bound piRNAs and nascent RNA determines the target specificity of piRNA‐dependent DNA methylation. piRNA‐dependent regions are transcribed at the developmental stage when piRNA‐mediated DNA methylation occurs. The MIWI2‐piRNA complex specifically interacts with RNAs transcribed from piRNA‐dependent regions. Removing a retrotransposon sequence either in a piRNA‐dependent region or a piRNA cluster abolishes DNA methylation of the piRNA‐dependent region. In Mili −/− prospermatogonia deficient in producing MIWI2‐bound piRNAs, de novo DNA methylation is compromised in many MIWI2‐dependent regions. Abstract : The piRNA pathway represses retrotransposons during early development. Base‐pairing between nascent RNA and piRNAs bound by mouse Piwi protein MIWI2 determines the specificity of suppressive DNA methylation.